A fluorescent carbonized polymer dot nanocomposite material and its preparation method and application

By using fluorescent carbonized polymer dot nanocomposites to display powder, the problems of low sensitivity, high cost and high toxicity in existing latent fingerprint display technology are solved, and efficient, non-toxic and low-cost latent fingerprint display and detection effects are achieved.

CN116445154BActive Publication Date: 2025-04-04ZHENGZHOU UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310449143.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-24
Publication Date
2025-04-04
Estimated Expiration
2043-04-24

AI Technical Summary

Technical Problem

The existing latent fingerprint display technology has problems such as low sensitivity, high cost and high toxicity, making it difficult to effectively display and detect potential fingerprints.

Method used

A fluorescent carbonized polymer dot nanocomposite was used to prepare a carbonized polymer dot solution by microwave heating method, and fixed it in the porous zeolite imidazole ester skeleton to form a fluorescent carbonized polymer dot nanocomposite powder for the display and detection of latent fingerprints.

Benefits of technology

The display effect is significant, the detection sensitivity is high, the material is non-toxic and low cost, and it can clearly display the multi-level detailed characteristics of fingerprints, which is suitable for latent fingerprint detection on different objects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004196916700000011
    Figure HDA0004196916700000011
  • Figure HDA0004196916700000012
    Figure HDA0004196916700000012
  • Figure HDA0004196916700000021
    Figure HDA0004196916700000021
Patent Text Reader

Abstract

The present invention discloses a fluorescent carbonized polymer dot nanocomposite material and a preparation method thereof. A yellow-green light emitting carbonized polymer dot solution is prepared by a microwave method, and the carbonized polymer dot solution is further fixed in a zeolite imidazolate framework by an in-situ self-assembly strategy to prepare a solid-state luminescent nanocomposite material, which effectively avoids the fluorescence quenching of the carbonized polymer dots in the solid state and the aggregated state. The nanocomposite material powder is dipped in a feather fingerprint brush to detect latent fingerprints left on different objects. A clear fingerprint image can be observed under an ultraviolet light source, and multi-level fingerprint detail features are detected, which is suitable for latent fingerprint detection at crime scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of forensic science trace inspection, and specifically relates to the preparation of a fluorescent carbonized polymer dot nanocomposite material and its application in latent fingerprint detection. Background Art

[0002] Fingerprints, or papillary patterns on the surface of the skin on the hands, are unique to humans (including primates) and have typical genetic traits. Fingerprints are obviously different, even the fingerprints of identical twins are different, and they are stable throughout life and reflect the traces left on objects. In forensic science, fingerprints are known as the "first evidence" of trace evidence. They can directly identify people and play an important role in case detection, court proceedings and public safety maintenance.

[0003] Normally, fingerprints obtained at a crime scene are divided into three types: visible fingerprints, indentation fingerprints, and latent fingerprints. Among them, latent fingerprints are the most common problem in on-site investigations. This type of fingerprint is difficult to distinguish and detect visually, and needs to be processed by physical or chemical means to make it visible before further individual identification can be carried out. Whether latent fingerprints can be effectively revealed directly determines whether the relevant cases can be quickly and accurately solved, and even prosecuted and tried. It is crucial to develop new latent fingerprint revealing technologies or revealing materials for rapid and non-destructive detection of latent fingerprints at crime scenes, which has important practical significance for conducting public security investigations and punishing criminals.

[0004] Traditional latent fingerprint visualization methods mainly include optical visualization (such as ultraviolet light inspection, laser inspection, etc.), powder brushing method, iodine fumigation method, AgNO3 method, ninhydrin method, 502 glue fumigation method, 1,8-diaza-9-fluorenone (DFO) method, etc. However, these methods still have disadvantages such as low sensitivity, high cost, and high toxicity, which make it difficult to identify and extract latent fingerprints at the crime scene; and in recent years, the luminescence detection technologies such as precious metal nanoclusters, semiconductor quantum dots, and rare earth upconversion nanomaterials that have gradually emerged in the forensic science community have defects such as high cost, complex process, and high toxicity, which limits the further application of nanoluminescent materials in the field of latent fingerprint visualization.

[0005] Carbonized polymer dots (CPDs) are a type of nanocarbon material composed of amorphous or crystalline carbonized polymer nanoparticles less than 10 nm. CPDs are widely used due to their simple, fast and cheap synthesis route, excellent water solubility, excellent optical properties and low toxicity. CPDs have strong luminescence performance, good photostability, simple synthesis method, abundant and cheap raw materials, and are expected to further improve the appearance of latent fingerprints. Therefore, it is very important to develop composite nanomaterials based on fluorescent carbonized polymer dots for the application of latent fingerprint appearance.

[0006] Using solid CPDs materials to detect latent fingerprints instead of traditional fingerprint powder can greatly improve the fingerprint visualization effect and reduce the harm to operators, while maintaining the on-site use advantage of the powder visualization method. However, the luminescence of CPDs in solid or aggregated state is easily severely quenched, and freeze-dried CPDs have extremely strong hygroscopicity, making it difficult to directly use the powder method for latent fingerprint visualization research. Using matrix-assisted stabilization of CPDs luminescence is expected to prepare fluorescent carbonized polymer dot nanocomposite powder. Summary of the invention

[0007] In order to solve the problems existing in the above-mentioned existing latent fingerprint display technology, the purpose of the present invention is to provide a fluorescent carbonized polymer dot nanocomposite material with simple preparation and low cost and a preparation method thereof; and to provide the application of the fluorescent carbonized polymer dot nanocomposite material in latent fingerprint display. The latent fingerprint display powder of the present invention has the characteristics of simple synthesis, convenient use, non-toxic and harmless, significant effect, etc., and the use of the latent fingerprint display powder of the present invention has excellent application value in the field of latent fingerprint display technology.

[0008] The detailed technical solution adopted by the present invention is as follows:

[0009] 1. Preparation of fluorescent carbonized polymer dot nanocomposites

[0010] The method for preparing the fluorescent carbonized polymer dot nanocomposite material of the present invention comprises the following steps:

[0011] (1) Take malic acid and fluorescent yellow, add anhydrous ethanol, and after completely dissolving, add guanidine carbonate and dimethyl sulfoxide solvent; after being fully mixed by ultrasound, vibration or stirring, react at 120-160° C. for 1-4 hours in a microwave oven; after the reaction is completed, cool to room temperature, filter, and then dialyze and purify in a dialysis bag for 24-72 hours; after evaporating the dialysate, continue to dissolve in the solvent to obtain a carbonized polymer dot solution;

[0012] Wherein, the mass ratio of malic acid, fluorescent yellow and guanidine carbonate is (10-30):6-12:(20-40);

[0013] (2) taking imidazole-2-carboxaldehyde, an organic amine and a surfactant, and uniformly dispersing them in a mixed solvent to obtain a solution A; weighing a certain amount of zinc salt, dissolving it in anhydrous ethanol, and then adding the carbonized polymer dot solution obtained in step (1), mixing them uniformly, to obtain a zinc salt solution containing carbonized polymer dots; then adding the zinc salt solution containing carbonized polymer dots to solution A, reacting at room temperature for 12 to 48 hours, to obtain a fluorescent carbonized polymer dot nanocomposite material.

[0014] The organic amine is selected from at least one of triethylamine and hexamethylenetetramine.

[0015] The surfactant is selected from at least one of polyvinyl pyrrolidone and cetyl trimethyl ammonium bromide.

[0016] The mixed solvent is a mixed solvent of dimethyl sulfoxide and water, and the volume ratio is (1-4):4.

[0017] The zinc salt is selected from at least one of zinc nitrate, zinc perchlorate and zinc acetate.

[0018] The dosage ratio of imidazole-2-carboxaldehyde, organic amine and surfactant is 1-3g:1.5-3mL:3-9g.

[0019] The dosage ratio of zinc salt to carbonized polymer dots is 1mmol:(5ug-5mg), and the molar ratio of zinc salt to imidazole-2-carboxaldehyde is 1:3-10.

[0020] The present invention rapidly prepares a carbonized polymer dot solution by microwave heating, and further fixes it in a porous zeolite imidazolate framework by a room temperature self-assembly method, and dries the obtained composite material to obtain a fluorescent carbonized polymer dot nanocomposite material. The formed composite material retains the fluorescence emission of the carbonized polymer dot itself in the solid state, and avoids the fluorescence quenching effect caused by the aggregation of carbonized polymer dot particles.

[0021] 2. The fluorescent carbonized polymer dot nanocomposite prepared by the present invention is used for latent fingerprint detection. The fluorescent carbonized polymer dot nanocomposite for latent fingerprint detection comprises the following steps:

[0022] (1) Grind the fluorescent carbonized polymer dot nanocomposite material evenly with a mortar, dip the powder with a feather fingerprint brush, flick it on the surface of the object where the latent fingerprint is located, gently shake the object, and after the fingerprint lines appear, blow away the excess powder along the fingerprint lines to obtain a fingerprint visible to the naked eye;

[0023] Among them, objects include glass, aluminum sheets, stainless steel, plastic, marble, wooden painted surfaces, banknotes or coins with concave and convex patterns, etc.;

[0024] (2) In a dark environment, the surface of the object where the latent fingerprint is located is illuminated with an excitation light source with a wavelength of 250-500nm, and a clear latent fingerprint image can be obtained by taking a photo. The latent fingerprints on different objects are detected using solid-state fluorescent carbonized polymer dot nanocomposites, and clear multi-level fingerprint details can be observed under ultraviolet light, which is suitable for fingerprint identification.

[0025] Compared with the prior art, the fluorescent carbonized polymer dot nanocomposite material latent fingerprint revealing powder of the present invention not only has a simple preparation process, convenient and quick operation, low toxicity, high luminous intensity, good stability, rapid revealing, wide application range, but also has high latent fingerprint detection accuracy and can clearly reveal the multi-level detail features of fingerprints. The fluorescent carbonized polymer dot nanocomposite material of the present invention not only has a huge driving effect on the development of efficient fingerprint detection materials, but also has great practical application value.

[0026] The beneficial effects of the present invention are:

[0027] 1. The latent fingerprint revealing effect of the present invention is significantly enhanced, and the detection sensitivity is significantly improved.

[0028] 2. The present invention can effectively overcome the interference of background fluorescence of the object.

[0029] 3. The fluorescent carbonized polymer dot nanocomposite material used in the present invention has little destructive effect on the DNA in the fingerprint material, and the fingerprint sample after inspection can be further subjected to DNA extraction and STR typing analysis.

[0030] 4. The fingerprint detection material and detection operation in the present invention can be realized at room temperature, with simple operation, rapid manifestation, low cost and non-toxic and harmless materials.

[0031] 5. The fingerprint detection material of the present invention not only has good fluorescence properties, but also has water response properties, and can change color in the presence of trace water, and can use the trace water secreted by the fingerprint sweat pores to visualize the fingerprint.

[0032] 6. The synthesis of carbonized polymer dot materials with hydrochromic properties by a simple one-step synthesis method for use in latent fingerprint detection is a new fingerprint detection strategy that has not been reported so far. The present invention can expand the synthesis strategy of hydrochromic latent fingerprint detection materials and provide a new direction for the design of hydrochromic latent fingerprint materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a transmission electron microscopy image of the fluorescent carbonized polymer dots prepared in Example 1 of the present invention.

[0035] Figure 2This is a fluorescence spectrum of the fluorescent carbonized polymer dots prepared in Example 1 of the present invention.

[0036] Figure 3 This is a scanning electron microscope image of the fluorescent carbonized polymer dot nanocomposite material prepared in Example 2 of the present invention.

[0037] Figure 4 This is a transmission electron microscope image of the fluorescent carbonized polymer dot nanocomposite material prepared in Example 2 of the present invention.

[0038] Figure 5 This is a photograph of the fluorescent carbonized polymer dot nanocomposite material prepared in Example 2 of the present invention under a sunlight source.

[0039] Figure 6 This is a photograph of the fluorescent carbonized polymer dot nanocomposite material prepared in Example 2 of the present invention under ultraviolet light.

[0040] Figure 7 This is a fluorescence spectrum of the fluorescent carbonized polymer dot nanocomposite material prepared in Example 2 of the present invention.

[0041] Figure 8 This is a latent fingerprint imaging image of the fluorescent carbonized polymer dot nanocomposite powder prepared in Example 2 of the present invention used on glass.

[0042] Fig. 9 This is a latent fingerprint imaging image of the fluorescent carbonized polymer dot nanocomposite powder prepared in Example 2 of the present invention on an aluminum sheet.

[0043] Fig.10 The fluorescent carbonized polymer dot nanocomposite powder prepared in Example 2 of the present invention is used for latent fingerprint imaging on coins.

[0044] Fig.11 This is a latent fingerprint imaging image of the fluorescent carbonized polymer dot nanocomposite powder prepared in Example 2 of the present invention used on a plastic cell culture dish.

[0045] Fig.12 This is a latent fingerprint imaging image of the fluorescent carbonized polymer dot nanocomposite powder prepared in Example 2 of the present invention used on marble. DETAILED DESCRIPTION

[0046] The following is a clear and complete description of the technical solution of the present invention in conjunction with the embodiments of the present invention. It is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Example 1: Preparation of fluorescent carbonized polymer dots

[0048] Weigh 20 mg of malic acid and 9 mg of fluorescent yellow powder, add 2 mL of anhydrous ethanol, sonicate for 5 minutes to completely dissolve, then add 27 mg of guanidine carbonate and 20 uL of dimethyl sulfoxide solvent, use a vortex oscillator to mix well, and transfer to a microwave reactor to react at 150 ° C for 1.5 hours. After the reaction is completed, the reaction solution is cooled to room temperature, filtered with a filter membrane, and then transferred to a 1Kd dialysis bag for dialysis purification for 48 hours. The dialysate is evaporated to dryness using a rotary evaporator to obtain a brown solid, which is further dissolved in dimethyl sulfoxide to obtain a carbonized polymer dot (CPDs-1) solution.

[0049] Comparative Example 1: The same synthesis method was used, but no fluorescent yellow raw material was added to the reaction system to synthesize a comparative carbonized polymer dot material. The specific synthesis process is as follows:

[0050] Weigh 20 mg of malic acid, add 2 mL of anhydrous ethanol, sonicate for 5 minutes to completely dissolve it, then add 27 mg of guanidine carbonate and 20 uL of dimethyl sulfoxide solvent, use a vortex oscillator to mix thoroughly, and transfer to a microwave reactor to react at 150 ° C for 1.5 hours. After the reaction is completed, the reaction solution is cooled to room temperature, filtered with a filter membrane, and then transferred to a 1Kd dialysis bag for dialysis purification for 48 hours. After the dialysate is evaporated to dryness using a rotary evaporator, the obtained solid is further dissolved in dimethyl sulfoxide to obtain a control group carbonized polymer dot solution (CPDs-2).

[0051] Transmission electron microscopy image of carbonized polymer dots CPDs-1 Figure 1 The results showed that the prepared carbonized polymer dots were approximately spherical, uniform in size, well dispersed, and the average particle size was 2.6 nm.

[0052] The carbonized polymer dots synthesized with fluorescent yellow and the polymer dots without fluorescent yellow dispersed in dimethyl sulfoxide both had a fluorescence emission near 450nm under ultraviolet light excitation. However, after diluting them with water, it was found that only the carbonized polymer dots with fluorescent yellow added had a double peak emission, and the other fluorescence peak was near 520nm. This is because in the presence of water, the fluorescent yellow lactam spirocyclic structure in the carbonized polymer dots undergoes a ring-opening reaction, restoring aromaticity and producing fluorescent emission. It can be seen that the carbonized polymer dot material we synthesized has a hydrochromic function and can be used for related water response research.

[0053] The fluorescence emission of carbonized polymer dots is shown in Figure 2 Under different excitation wavelengths, the carbonized polymer dots showed obvious double-peak emission, and the emission peak did not move significantly with the change of the excitation wavelength, indicating that the photoluminescence of the carbonized polymer dots was not dependent on the excitation wavelength.

[0054] Example 2: Preparation of fluorescent carbonized polymer dot nanocomposite materials

[0055] Weigh 1g of imidazole-2-carboxaldehyde and 3g of polyvinyl pyrrolidone, add 1.5mL of triethylamine and 5mL of a mixed solvent of dimethyl sulfoxide and water (volume ratio of 1:4), and ultrasonicate for 10 minutes to completely disperse it to obtain an imidazole-2-carboxaldehyde solution. Weigh 0.8g of zinc perchlorate hexahydrate, dissolve it in 10mL of anhydrous ethanol, and add 5, 10, 15 and 20uL of the carbonized polymer dot solution prepared in Example 1 (concentration of 10mg / mL), respectively, mix well, and obtain a zinc salt solution containing carbonized polymer dots. Under vigorous stirring or ultrasonic conditions, add the zinc salt solution containing carbonized polymer dots to the imidazole-2-carboxaldehyde solution and react at room temperature for 24 hours. After the reaction is completed, the obtained solid is centrifuged and dried, ground into powder with a mortar, and placed in a brown glass bottle for standby use, marked as A1.

[0056] The scanning electron microscopy and transmission electron microscopy images of fluorescent carbonized polymer dot nanocomposites are shown in Figure 2. Figure 3 and Figure 4 As shown in Figure 3, the carbonized PDot composite material maintains the regular polygonal morphology of the imidazolate skeleton. Figure 5 The carbonized polymer dot composite material appears light yellow under sunlight and emits green light when excited by ultraviolet light in a dark environment ( Figure 6 ). The fluorescence spectra of the composite materials prepared with different addition amounts of carbonized polymer dots are shown in Figure 2. Figure 7 , their fluorescence emission wavelengths are similar, retaining the original luminescence characteristics of carbonized polymer dots, showing double-peak emission, with emission peaks at 453nm and 518nm respectively.

[0057] Comparative Example 2: A carbonized polymer dot composite material with a similar metal organic framework structure was synthesized by a similar synthesis method. The specific synthesis method is as follows: Weigh 0.8g 2-methylimidazole and 3g polyvinyl pyrrolidone, add 1.5mL triethylamine and 5mL dimethyl sulfoxide and water mixed solvent (volume ratio is 1:4), and ultrasonicate for 10 minutes to completely disperse it. Weigh 0.8g zinc perchlorate hexahydrate (or 0.6g cobalt nitrate hexahydrate), dissolve it in 10mL anhydrous ethanol, and add 5, 10, 15 and 20uL carbonized polymer dot solution respectively, and mix well. Under vigorous stirring or ultrasonic conditions, the zinc salt solution containing carbonized polymer dots is added to the imidazole-2-formaldehyde solution and reacted for 24 hours. After the reaction is completed, the obtained solid is centrifuged and dried, ground into powder with a mortar, and placed in a brown glass bottle for standby use, marked as D1 (or D2).

[0058] Fluorescence testing found that the obtained nanocomposites D1 and D2 did not have fluorescence emission, which may be due to the inability to connect the carbonized polymer dots to the metal organic framework through covalent bonds, resulting in the aggregation of carbonized polymer dots in the metal organic framework and causing fluorescence quenching. When imidazole-2-carboxaldehyde ligands are used, the amino groups in the carbonized polymer dots can form covalent bonds with the aldehyde groups, and the carbonized polymer materials are evenly dispersed on the metal organic framework, avoiding fluorescence quenching.

[0059] Example 3: Fluorescent carbonized polymer dot nanocomposite material for latent fingerprint visualization on glass

[0060] Dip the fluorescent carbonized polymer dot nanocomposite powder prepared in Example 2 with a feather fingerprint brush, and gently flick it onto the glass surface where the latent fingerprint is located. Shake the glass to allow the carbonized polymer dot nanocomposite to evenly cover the latent fingerprint. Then use an ear cleaning bulb or an air gun to blow in the same direction. After the fingerprint lines appear, blow along the lines to remove excess unbound powder. The latent fingerprint after exposure is placed under a 365nm ultraviolet light source, and take a photo to fix the latent fingerprint on the glass. Figure 8 As shown, a bright green fingerprint image with clear lines can be obtained under ultraviolet light source, and the fingerprint lines are clear.

[0061] Example 4: Fluorescent carbonized polymer dot nanocomposite material for latent fingerprint visualization on aluminum sheet

[0062] According to the latent fingerprint detection method of Example 3, the fluorescent carbonized polymer dot nanocomposite powder prepared in Example 2 was used for latent fingerprint detection on an aluminum sheet. The detection results are as follows: Fig. 9 As shown in the figure, a bright green fingerprint image with clear lines can be obtained under ultraviolet light, and the sweat pore features are clearly visible.

[0063] Example 5: Fluorescent carbonized polymer dot nanocomposite material for latent fingerprint visualization on coins

[0064] According to the latent fingerprint detection method of Example 3, the fluorescent carbonized polymer dot nanocomposite material display powder prepared in Example 2 was used for latent fingerprint detection on coins. The results are as follows: Fig.10 As shown. Under ultraviolet light, a bright green fingerprint image with clear lines can be obtained.

[0065] Example 6: Fluorescent carbonized polymer dot nanocomposite material for latent fingerprint visualization on plastic cell culture dishes

[0066] According to the latent fingerprint detection method of Example 3, the fluorescent carbonized polymer dot nanocomposite material display powder prepared in Example 2 was used for latent fingerprint detection on a plastic cell culture dish. The results are as follows: Fig.11As shown. Under ultraviolet light, a bright green fingerprint image with clear lines can be obtained.

[0067] Example 7: Fluorescent carbonized polymer dot nanocomposite material for latent fingerprint visualization on marble

[0068] According to the latent fingerprint detection method of Example 3, the fluorescent carbonized polymer dot nanocomposite material display powder prepared in Example 2 was used for latent fingerprint detection on marble. The results are as follows: Fig.12 As shown. Under ultraviolet light, a bright green fingerprint image with clear lines can be obtained.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fluorescent carbonized polymer dot nanocomposite material, comprising the following steps: (1) Take malic acid and fluorescent yellow, add anhydrous ethanol, and after completely dissolving, add guanidine carbonate and dimethyl sulfoxide solvent; after being fully mixed by ultrasound, vibration or stirring, react at 120-160° C. for 1-4 hours in a microwave oven; after the reaction is completed, cool to room temperature, filter, and then dialyze and purify in a dialysis bag for 24-72 hours; after evaporating the dialysate, continue to dissolve in the solvent to obtain a carbonized polymer dot solution; (2) taking imidazole-2-carboxaldehyde, an organic amine and a surfactant, and uniformly dispersing them in a mixed solvent to obtain a solution A; weighing a certain amount of zinc salt, dissolving it in anhydrous ethanol, and then adding the carbonized polymer dot solution obtained in step (1), mixing them evenly, to obtain a zinc salt solution containing carbonized polymer dots; then adding the zinc salt solution containing carbonized polymer dots to solution A, reacting at room temperature for 12 to 48 hours, to obtain a fluorescent carbonized polymer dot nanocomposite material; in step (1), the mass ratio of malic acid, fluorescent yellow and guanidine carbonate is (10-30):6-12:(20-40).

2. The method for preparing a fluorescent carbonized polymer dot nanocomposite material according to claim 1, characterized in that: In step (2), the organic amine is selected from at least one of triethylamine and hexamethylenetetramine; the surfactant is selected from at least one of polyvinylpyrrolidone and hexadecyltrimethylammonium bromide; and the zinc salt is selected from at least one of zinc nitrate, zinc perchlorate and zinc acetate.

3. The method for preparing a fluorescent carbonized polymer dot nanocomposite material according to claim 1, characterized in that: In step (2), the mixed solvent is a mixed solvent of dimethyl sulfoxide and water, and the volume ratio is (1-4):

4.

4. The method for preparing a fluorescent carbonized polymer dot nanocomposite material according to claim 1, characterized in that: In step (2), the usage ratio of imidazole-2-carboxaldehyde, organic amine and surfactant is 1-3 g:1.5-3 mL:3-9 g.

5. The method for preparing a fluorescent carbonized polymer dot nanocomposite material according to claim 1, characterized in that: In step (2), the ratio of zinc salt to carbonized polymer dots is 1 mmol:(5 ug-5 mg), and the molar ratio of zinc salt to imidazole-2-carboxaldehyde is 1:3-10.

6. Use of the fluorescent carbonized polymer dot nanocomposite material according to any one of claims 1 to 5 in latent fingerprint visualization.

7. The use according to claim 6, characterized in that: The detection of latent fingerprints by fluorescent carbonized polymer dot nanocomposites includes the following steps: (1) Grinding the fluorescent carbonized polymer dot nanocomposite material into powder using a mortar, dipping the powder with a feather brush, gently flicking the powder onto the surface of the object where the latent fingerprint is located, shaking and blowing the surface of the object where the latent fingerprint is located, and obtaining a fingerprint visible to the naked eye; (2) Illuminate the surface of the object where the latent fingerprint is located with an excitation light source, and take a picture to obtain a clear latent fingerprint image.

8. The use according to claim 7, characterized in that: The wavelength range of the excitation light source is 250-500nm.

9. The use according to claim 7, characterized in that: The object includes glass, aluminum sheet, stainless steel, plastic, marble, wooden painted surface or coins and banknotes with concave and convex patterns.

Citation Information

Patent Citations

  • Compositions and methods to prevent and treat biofilms

    CA3088187A1

  • Cell modulation nanocomposition, and methods of use

    CN106414723A